ROLE OF PHYSICAL ENVIRONMENT TO ORIENTATION AND MOBILITY OF BLIND IN PSBN WYATA GUNA BANDUNG (Jurnal Riset Arsitektur, 2018)
Abstract- Visually impaired is a general term to describe the condition of a person experiencing disability to their sense of sight. Due to the disability, the process of orientation and mobility of the people with visually impairment is inhibited. Therefore they try to increase their sensitivity of other senses like sense of touch, sense of smell, and sense of hearing to obtain information from the surrounding physical environment. PSBN Wyata Guna is a residential for the visually impaired, as the physical environment it must have physical elements that can provide information which affect effectivelly to the orientation and mobility of the visually impaired. The purpose of this study is to find out what physical elements in the environment of PSBN Wyata Guna that affect the orientation and mobility of the visually impaired and how effective the influence of these elements.This study use qualitative descriptive methods by mapping the behavior of fourteen respondents (person-centered mapping) who do orientation and mobility in the physical environment of PSBN Wyata Guna. Physical environments are classified based on elements that define the space, ie horizontal and vertical planes, which is, tactile pavements, materials differences, Ramps, steps, corridor columns, ceramic walls, shrubs, and hand railling. Observations held on Saturday and Sunday in the morning-afternoon when most of visually impaired do their activities outside the dorm.The result of this research shows that  people with visual impairment in the environment of PSBN Wyata Guna use the physical environment to obtain information for their orientation and mobility. This orientation and mobility activity is mostly affected by tactile pavements, ceramic walls, and Ramps. Shrubs and hand railling have less role to the orientation and mobility of the visually impaired. Thus, it can be concluded that the physical environment of PSBN Wyata Guna is influential in the orientation and mobility of the visually impaired. Key Words: orientation and mobility, visually impaired, physical environments, physical elements, PSBN Wyata Guna